Complement C7 and clusterin form a complex in circulation - Massri, Mariam; Toonen, Erik J.M.; Sarg, Bettina; Kremser, Leopold; Grasse, Marco; Fleischer, Verena; Torres-Quesada, Omar; Hengst, Ludger; Skjoedt, Mikkel-Ole; Bayarri-Olmos, Rafael; Rosbjerg, Anne; Garred, Peter; et al. (Frontiers in Immunology, 2024)
The complement system is part of innate immunity and is comprised of an intricate network of proteins that are vital for host defense and host homeostasis. A distinct mechanism by which complement defends against invading pathogens is through the membrane attack complex (MAC), a lytic structure that forms on target surfaces. The MAC is made up of several complement components, and one indispensable component of the MAC is complement C7. The role of C7 in MAC assembly is well documented, however, inherent characteristics of C7 are yet to be investigated. To shed light on the molecular characteristics of C7, we examined the properties of serum-purified C7 acquired using polyclonal and novel monoclonal antibodies. A series of proteolytic analyses of serum-purified C7, encompassing Western blot and mass spectrometry analysis, showcased C7 in association with clusterin, an inhibitory complement regulator. The distinct association between C7 and clusterin was also demonstrated in serum-purified clusterin. Clusterin dissociates the MAC structure by binding to polymerized C9, nevertheless, clusterin binding to the native form of terminal complement proteins has not yet been showcased in vivo. Further assessment of the relationship between C7 and clusterin was assessed via an established enzyme-linked immunosorbent assay (ELISA), in which a complex between C7 and clusterin (C7-CLU) was detected. The C7-CLU complex was also identified in healthy serum and plasma donors, as well as in serum fractionated by size exclusion chromatography, further verifying the presence of this protein complex in circulation. The presented data reveal that C7 exhibits characteristics beyond that of MAC assembly, instigating further investigation of the effector role that the C7-CLU complex plays in the complement cascade.